An Analysis of the Purpose and Causes of the “Central Discourse” in Islām: A Study from Historic to Contemporary Era - Kattoua, Mohamad Turky (Journal of Islamic and Religious Studies, 2019)
The wasaṭiyyah (Islamic moderation) concept is deep-rooted in Islam. It is a straight path, a good between two evils; it maintains balance between the two extremes of excess and deficiency, and between fanaticism and negligence. Moderation was widely practiced with the advent of Islam. It was a noteworthy aspect of people’s day to day life and conducts. The term wasaṭiyyah (moderation) emerged in the early eighties. It was initially introduced by Shiekh Yūsuf Al-Qaraḍāwī. He used it in his books and discourses, and gradually it become very prevalent. Few factors resulted in widespread use of the term, the main factor is the western systematic campaign against Islam and Muslims to distort their image and label them with terrorism and extremism. Therefore, they frequently used the term wasaṭiyyah to prove themselves against these accusations. Another factor is the current situation in most Muslim countries and their struggle with social and political injustice which turns Muslim youth to extremism and terrorism that is why Muslim scholars and reformers, through their moderate discourse, stood up and condemned fanaticism and radical ideology. All that made the term wasaṭiyyah widely used by different people from all walks of life, and each has its aims and intentions behind embracing the moderate discourse and raising the flag of wasaṭiyyah (moderation).